The relationship between organizational climate, job stress, workplace burnout, and retention of pharmacists - Lan, Yu‐Li; Huang, Wan‐Tsui; Kao, Chi‐Lan; Wang, Hui‐Jung (Journal of occupational health, 2020)
Objectives This study explored the relationship between organizational climate, job stress, workplace burnout, and retention of pharmacists. This study adopted a cross‐sectional design and conducted a questionnaire survey of pharmacists working at three teaching hospitals (a district teaching hospital, a regional teaching hospital, and a medical center). Methods The sampling criteria were a license to practice pharmacy and a willingness to sign a written consent form to participate in this study. Results One hundred ten questionnaires were distributed, of which 101 contained valid responses, yielding a valid return rate of 91.82%. A significant correlation was evident between organizational climate, job stress, workplace burnout, and retention. Hierarchical regression analysis revealed that demographic variables, organizational climate, job stress, and workplace burnout had a predictive power of 55.6% for retention (F = 9.712***, P < .001). Organizational climate had a significant positive correlated with retention (β =  0.401*, P < .001). Conclusions The results of this study can help hospitals to create a friendly and healthy workplace, instruct hospital managers how to improve their organizational climates, and reduce pharmacists’ job stress and workplace burnout, thereby enhancing the quality of pharmacy service and medication safety and eventually improving pharmacists’ intention to stay.